DAMPAK TEKNOLOGI INFORMASI DALAM PENGENDALIAN INTERNAL UNTUK MENGANTISIPASI KECENDERUNGAN KECURANGAN AKUNTANSI - Korompis, Claudia (JURNAL RISET AKUNTANSI GOING CONCERN, 2014)
Fraud or Cheating is an act of deliberate dishonesty to deprive the rights or property of people / other party. In the context of the audit of financial statements, fraud is defined as the misstatements in the financial statements are done on purpose. Companies that were identified to be cheating may result in bankruptcy. Here, the role of the internal control system is needed. Management of designing a system of internal controls so that they mendapatakan reliability of financial reports, the efficiency and effectiveness of operations, and compliance with laws and regulations. In the Modern Era, an internal control system can not be separated from the development of Information Technology. When developing a business enterprise and the need for increased information, usually the company will increase its IT systems. The advantages of information technology is its ability to handle complex business transactions in the sheer number of large efficiently. With the good information technology would significantly reduce the opportunity to commit fraud (Elder, Beasley, Arens, Jusuf: 2013).